1985
DOI: 10.1002/kin.550171004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and kinetics of the silane decomposition in the presence of acetylene and in the presence of olefins

Abstract: Kinetic data and product studies are reported for the silane pyrolysis in the presence of olefins and acetylene. The kinetics of silane loss in the presence of acetylene was found to be identical to the initial gas phase silane decomposition step (SiH4 + M + SiH, + H2 + M) when corrected for pressure fall-off effects. This result and the absence of methane or ethane from the pyrolysis of SiH4 in the presence of 1-butene or 1-pentene demonstrate that silyl radicals and H atoms are not involved in silane-olefin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
16
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 14 publications
8
16
0
Order By: Relevance
“…Rice, Ramsperger, Kassel, Marcus (RRKM) theoretical modelling studies of these pressure dependencies have shown them to be consistent with the formation of silirane and silirene rings and the experimental results have yielded information about the strain energies of these rings. Isotopic labelling studies 18,19,24,25 have revealed the presence of scrambling mechanisms consistent with facile and reversible ring opening reactions of siliranes and silirenes leading to formation of isomeric alkyl-and alkenyl-silylenes, as suggested by earlier product analytical studies, [26][27][28][29][30][31] and supported by theoretical calculations. [32][33][34][35] We have recently studied the kinetics of GeH 2 + C 2 H 4 13 and GeH 2 + C 3 H 6 11 and shown that they are broadly consistent with formation of germirane products.…”
Section: Introductionsupporting
confidence: 61%
“…Rice, Ramsperger, Kassel, Marcus (RRKM) theoretical modelling studies of these pressure dependencies have shown them to be consistent with the formation of silirane and silirene rings and the experimental results have yielded information about the strain energies of these rings. Isotopic labelling studies 18,19,24,25 have revealed the presence of scrambling mechanisms consistent with facile and reversible ring opening reactions of siliranes and silirenes leading to formation of isomeric alkyl-and alkenyl-silylenes, as suggested by earlier product analytical studies, [26][27][28][29][30][31] and supported by theoretical calculations. [32][33][34][35] We have recently studied the kinetics of GeH 2 + C 2 H 4 13 and GeH 2 + C 3 H 6 11 and shown that they are broadly consistent with formation of germirane products.…”
Section: Introductionsupporting
confidence: 61%
“…Its parent radical, SiH 3 , is of great importance in chemical vapor deposition processes. 11,12 The silyl cation, SiH 3 ϩ , is one of the most abundant ions in silane plasmas, and thus it has been studied in considerable detail, its properties 13 and ionmolecule reactions 14,15 being quite well understood by now. The structure of SiH 3 Ϫ is expected to be similar to that of NH 3 , one of the most extensively studied molecules of structural chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…A question is raised whether secondary dissociation of the ethylsilylene radical via reaction (3) is not a more likely source of Sill2 than primary dissociation of ethylsilane via reaction (1). Recent experimental work by Knight and co-workers [1][2][3] suggests that there may be two origins of silicon atoms from IRMPD studies of n-butysilane: one from Sill2 and the other from n-butylsilylene. In this work, decomposition pathways of ethylsilylene which lead to the formation of silicon atoms are explored.…”
Section: Introductionmentioning
confidence: 97%
“…In the production of amorphous silicon thin films for microelectronic manufacture, silicon hydrides such as silane (Sill4) and disilane (Si2Hr) are used as standard substrates [1][2][3]. Other substrates such as organosilanes are considered as possible alternatives provided their film deposition rates are faster than the silicon hydrides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation